Aleukemic Leukemia Cutis: Case Report and Review of Literature - Karam, Dhauna; Agrawal, Bharat (Indian Journal of Medical and Paediatric Oncology, 2018)
Aleukemic leukemia cutis (LC) is an extremely rare clinical presentation. All patients eventually develop acute leukemia, mostly monocytic and myelomonocytic types. It is a diagnostic challenge, resolved by careful immunophenotyping and cytochemistry. The diagnosis indicates a poor prognosis. Here, we report a case of an 85-year-old white male with LC, who had normal peripheral blood and bone marrow histology. The fragility of our patient precluded any definite anti-leukemic therapy.
Keywords: Acute myeloid leukemia; cytochemistry; histology in leukemia; immunophenotyping; leukemia cutis